2021
DOI: 10.1590/1806-9061-2019-1045
|View full text |Cite
|
Sign up to set email alerts
|

Production Performance and Egg Quality of Laying Hens as Influenced by Genotype and Rearing System

Abstract: The aim of this study was to evaluate the effect of rearing systems and genotypes on production performance and egg quality. Isa Brown and New Hampshire genotypes were used in this study. These two genotypes were housed in floor and organic rearing systems. During the experimental period, which lasted one year (52 weeks), the following production performance parameters were recorded: egg production, daily egg mass, feed consumption, feed conversion efficiency, and mortality. Fifteen eggs per group were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 33 publications
(36 reference statements)
2
4
0
Order By: Relevance
“…In the present study, signi cantly higher HU was observed in round eggs compared to sharp eggs in HEN and this was consistent with Duman et al (2016). This may be related to the larger size (hence higher albumen proportion) of round eggs compared to sharp eggs in this genotype and this agreed with the ndings of previous studies (Leiboldt et al, 2018;Nolte et al, 2021;Rakonjac et al, 2021).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, signi cantly higher HU was observed in round eggs compared to sharp eggs in HEN and this was consistent with Duman et al (2016). This may be related to the larger size (hence higher albumen proportion) of round eggs compared to sharp eggs in this genotype and this agreed with the ndings of previous studies (Leiboldt et al, 2018;Nolte et al, 2021;Rakonjac et al, 2021).…”
Section: Resultssupporting
confidence: 93%
“…The signi cantly improved EW in ginger group could be responsible for the improvement in EL, ESA, and EV observed in this group and this could be attributed to the health promoting effects of ginger probably due to its content of bene cial bioactive compounds (Nemati et 2023) however, reported nonsigni cant effect of ginger on ESI at 8 weeks of lay but signi cant effect at 10 weeks of lay which suggests an age dependent effect. Genotypic differences in YW and YR as were observed in the present study agreed with previous studies (Nolte et al, 2021;Rakonjac et al, 2021;. The higher YW in SB eggs is attributable to the larger egg size however; these eggs had lower YR compared to HEN eggs indicating that selection for higher egg size (egg weight) in hens may not proportionately improve egg yolk content.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Skrbic et al, 2011;Rakonjac et al, 2021). The perfect positive correlation of ED with ESA and EV in HEN were in agreement withAlkan et al (2015) andTyasi et al (2022).…”
mentioning
confidence: 59%
“…3,10,14 The ISA Brown (IB) hens are a popular commercial hybrid chicken known globally for their outstanding egg-laying performance. 15,16 The Green-legged Partridge (GLP) hens are a popular Polish native breed of chicken that are reared for both egg and meat production. 17,18 Although their laying performance is much lower compared to IB hens, eggs from GLP hens are gaining popularity due to their high nutritive and sensory value as well as being perceived as "organic".…”
Section: ■ Introductionmentioning
confidence: 99%